Motivasi dan Anjuran Dakwah dalam Perspektif Hadis - Aria Anggara (Gunung Djati Conference Series, 2023)
This study aims to discuss the hadith about da'wah. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about da'wah in the history of Ahmad No. 1949. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi fulfills the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Ahmad No. 1949 relevant to be used as motivation and development in the field of da'wah.